1993
DOI: 10.1111/j.1600-0528.1993.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of areca nut chewers among junior high school students in Changhua county, Taiwan

Abstract: Some studies indicate that betel quid and its ingredients chewing can produce cell mutagenicity and tumorigenicity. In Taiwan studies, betel quid chewing is the main cause of submucous fibrosis and oral cancer. Understanding the distribution and characteristics of the areca nut chewing population is one of the first steps in the effort to prevent these oral diseases. A stratified cluster random sample of 2442 junior high school students in Changhua county, Taiwan, were surveyed for the habit of areca nut chewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 11 publications
3
27
0
Order By: Relevance
“…The prevalence of betel nut chewing among adolescents has been investigated by researchers such as Ko et al [2], who found that the socioeconomic characteristics of betel nut chewing was related to having less-educated elders, blue-collar workers, and people who had the dual habits of smoking cigarettes and drinking alcohol. Lu et al [3], who studied the prevalence rate and the characteris-…”
Section: Apparently It Is Indicated That There Is a Significant Intementioning
confidence: 99%
“…The prevalence of betel nut chewing among adolescents has been investigated by researchers such as Ko et al [2], who found that the socioeconomic characteristics of betel nut chewing was related to having less-educated elders, blue-collar workers, and people who had the dual habits of smoking cigarettes and drinking alcohol. Lu et al [3], who studied the prevalence rate and the characteris-…”
Section: Apparently It Is Indicated That There Is a Significant Intementioning
confidence: 99%
“…However, this situation has changed, where in most parts of the Southeast Asia, the habit of betel quid chewing is slowly disappearing and is practised only among the older generation. However, in other countries such as in Taiwan, an increased number of betel quid chewers is found among the adolescence (5). It is also observed that in India this habit has been picked up by the younger generation due to the commercial product pan masala (containing areca nut) and gutka (containing areca nut and tobacco) (6).…”
Section: Introductionmentioning
confidence: 92%
“…The preparation for betel quid also varies from country to country. For example in Taiwan they usually chew betel nut with a lengthwise piece of unripe fruit with betel piper leaf and lime paste between the two halves of the nut (5). Chinese traditional herbs may be added but tobacco leaves are excluded.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations